2001
DOI: 10.1054/bjoc.2001.2171
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin AG 1024 modulates radiosensitivity in human breast cancer cells

Abstract: Summary Insulin-like growth factor-1 (IGF-1) plays an important growth-promoting effect by activating the PI3K/Akt signalling pathway, inhibiting apoptotic pathways and mediating mitogenic actions. Tyrphostin AG 1024, one selective inhibitor of IGF-1R, was used to evaluate effects on proliferation, radiosensitivity, and radiation-induced cell apoptosis in a human breast cancer cell line MCF-7. Exposure to Tyrphostin AG 1024 inhibited proliferation and induced apoptosis in a time-dependent manner, and the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 32 publications
(16 reference statements)
2
50
0
1
Order By: Relevance
“…Used in a concentration that specifically inhibited IGF-1R, AG1024 increased radiosensitivity of U1810 cells. Downstream consequences of IGF-1R activation were examined by selectively inhibiting PI3-K and p38 kinase, previously identified as IGF-1R mediators of cytoprotective responses after radiation (Heron-Milhavet et al, 2001;Wan et al, 2001;Wen et al, 2001). In accordance with other studies, we found that both p38 kinase and PI3-K inhibition induced radiosensitivity in IGF-1-stimulated U1810 cells, indicating that these proteins were part of IGF-1R signaling in response to radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Used in a concentration that specifically inhibited IGF-1R, AG1024 increased radiosensitivity of U1810 cells. Downstream consequences of IGF-1R activation were examined by selectively inhibiting PI3-K and p38 kinase, previously identified as IGF-1R mediators of cytoprotective responses after radiation (Heron-Milhavet et al, 2001;Wan et al, 2001;Wen et al, 2001). In accordance with other studies, we found that both p38 kinase and PI3-K inhibition induced radiosensitivity in IGF-1-stimulated U1810 cells, indicating that these proteins were part of IGF-1R signaling in response to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we described the IGF-1R involvement in cell protection from radiation-induced cell death (Cosaceanu et al, 2005). Blocking of IGF-1R activity by tyrosine kinase inhibitors or by anti-IGF-1R-neutralizing antibodies was shown to increase radiosensitivity in several types of human tumor cell lines (Wen et al, 2001;Cosaceanu et al, 2005). Nevertheless, the effect of radiation on IGF-1R activation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were lysed with 20 mM Tris, pH 7.5, 0.27 M sucrose, 1 mM EdTA, 1 mM EGTA, 1% Triton X-100 and protease/phosphatase inhibitors. Anti-B-Raf or c-Raf antibodies (1 µg) was added to the cell lysates and extracts were incubated in the cold for 1 h with mixing (21). Protein-G-Sepharose bead suspension (40 µl) was added to each vial and reactions were incubated at 4˚C in a head-to-head mixer for 2 h. Precipitates were washed using lysis buffer supplemented with 0.6 M NaCl.…”
Section: Measurement Of Apoptosis Apoptosis Was Examined With Thementioning
confidence: 99%
“…Selective inhibitors of the IGF-1 receptor also inhibit proliferation and enhance apoptosis by increasing the response of tumour cells to ionising radiation 165 The IGF-1 receptor can also be targeted by small molecular inhibitors of the IGF-1R tyrosine kinase, and molecular agents such as antisense and small interfering Somatostatin analogues exert antiproliferative effects both in vivo and in vitro, in part by inhibiting GH release and therefore reducing IGF-I levels, eg octreotide reduces breast cancer growth by 50% in mice 3 .…”
Section: Clinical Potentialmentioning
confidence: 99%